Effect of Physical Activity on Drug Craving of Women With Substance Use Disorder in Compulsory Isolation: Mediating Effect of Internal Inhibition - Wang, Kun; Luo, Jiong; Zhang, Tingran; Ouyang, Yiyi; Zhou, Chenglin; Lu, Yingzhi (Frontiers in Psychology, 2019)
Background: Women with substance use disorder has attracted widespread attention as a prominent social issue. According to reports, physical exercise can improve the internal inhibition, effectively reduce the substance user's drug graving, and improve withdrawal symptoms, However, the specific mechanism of internal inhibition should be further considered. This study was designed to determine the critical role of internal inhibition in the path of physical exertion affecting the drug cravings of women drug users. Methods: By means of Physical Activity Rating Scale (PARS-3), internal Inhibition Scale and Drug Craving Scale, this study investigated the individuals with substance use disorder under rehabilitation in the women compulsory isolation rehabilitation center in Chongqing, China. Results: 1) Women with traditional drug users had the strongest internal inhibition and new drug use disorder had the highest drug craving. The longer the duration of drug abuse, the lower the internal inhibition and the higher the drug craving. Women with moderate-intensity activity had the strongest internal inhibition and the lowest drug craving. 2) The physical activity intensity was negatively correlated with drug craving, positively correlated with intrinsic inhibition, and negatively correlated with drug craving. 3) Internal inhibition played a partial mediating effect between physical activity intensity and drug craving. Conclusion: Physical activity has a positive effect on inhibiting drug craving among drug addicts, while moderate-intensity activity seems to be more conducive to enhancing the internal inhibition of addicts, to improving their resistance to drugs, and thus more conducive to reducing drug craving.